Effects of flavonoids on rumen fermentation activity, methane production, and microbial population. - Oskoueian, Ehsan; Abdullah, Norhani; Oskoueian, Armin (Hindawi Publishing Corporation, 2013)
This research was carried out to evaluate the effects of flavone, myricetin, naringin, catechin, rutin, quercetin, and kaempferol at the concentration of 4.5% of the substrate (dry matter basis) on the rumen microbial activity in vitro. Mixture of guinea grass and concentrate (60 : 40) was used as the substrate. The results showed that all the flavonoids except naringin and quercetin significantly (P < 0.05) decreased the dry matter degradability. The gas production significantly (P < 0.05) decreased by flavone, myricetin, and kaempferol, whereas naringin, rutin, and quercetin significantly (P < 0.05) increased the gas production. The flavonoids suppressed methane production significantly (P < 0.05). The total VFA concentration significantly (P < 0.05) decreased in the presence of flavone, myricetin, and kaempferol. All flavonoids except naringin and quercetin significantly (P < 0.05) reduced the carboxymethyl cellulase, filter paperase, xylanase, and β-glucosidase activities, purine content, and the efficiency of microbial protein synthesis. Flavone, myricetin, catechin, rutin, and kaempferol significantly (P < 0.05) reduced the population of rumen microbes. Total populations of protozoa and methanogens were significantly (P < 0.05) suppressed by naringin and quercetin. The results of this research demonstrated that naringin and quercetin at the concentration of 4.5% of the substrate (dry matter basis) were potential metabolites to suppress methane production without any negative effects on rumen microbial fermentation.